Bimbingan Konseling Islam dalam Meningkatan Kedisiplinan Santri : Studi Kasus di Pondok Pesantren Hidayatut Thullab Petuk Kediri - Ulwiyah, Alhasan; Imron, Ali (Lembaga Penelitian, Publikasi dan Pengabdian Masyarakat (LP3M) UIT Lirboyo Kediri, 2022)
Planting discipline no could forced by direct or with punished only. Guidance Islamic counseling needed in embed discipline because Guidance Islamic counseling studied and researched as means for help individual in order to develop in tune with purpose man created. Study this aim for knowing guidance counseling counseling at the boarding school in handle problem discipline. Researcher this held at the cottage boarding school Hidayatut Thullab Petuk Kediri. Guidance Islamic counseling in handle discipline that is with approach Act in demand that is with understand behavior Students in change Act in demand through the learning process. In Case this, kyai, wali asuh, ustadz more play a role more active in effort change behavior student. As well as in overcome something worry with suppose existence working mechanisms for avoid overflow worry student.